Synthesis, Novel Crystal Structure, and β-Amyloid Binding Property of Re(I) (tricarbonyl)+ EHIDA Analogue - Yang Yang; Jia Xin Zhang; Lin Zhu; Huabei Zhang (Bioinorganic Chemistry and Applications)
A neutral compound Re(CO)3(L) (L: 2-((2-(2,6-diethylphenylamino)-2-oxoethyl)(2-ethoxy-2-oxoethyl)amino)acetic acid, an IDA analogue) has been synthesized and evaluated for in vitro imaging probes of β-amyloid (Aβ) aggregates. Results of X-ray measurement of Re(CO)3(L) demonstrated that the coordination mode of Re(CO)3(L) was different from that of classical Re/Tc(I) (tricarbonyl)-IDA analogues; the structure of Re(CO)3(L) was confirmed by means of infrared spectrum, HPLC-UV, TOF MS, and X-ray measurements (Cambridge Crystallographic Data Centre number is 732731): monoclinic P21/c, a=15.6636 (12) Å, b=10.9360 (8) Å, c=27.756 (2) Å, α=90.000 (0)∘, β=90.783 (5)∘, γ=90.000 (0)∘, and Z=8. The binding affinity for β-amyloid plaques was assessed by in vitro binding assay using preformed synthetic Aβ(1–40) aggregates. The neutral compound Re(CO)3(L) showed binding affinity to Aβ aggregates at micromolar level by fluorescence spectroscopy, and this work will encourage for further exploration of imaging agents labeled by T99mc(CO)3+ center as probes for β-amyloid plaques in vivo.